2014
DOI: 10.1371/journal.pone.0102763
|View full text |Cite
|
Sign up to set email alerts
|

Novel TCAP Mutation c.32C>A Causing Limb Girdle Muscular Dystrophy 2G

Abstract: TCAP encoded telethonin is a 19 kDa protein, which plays an important role in anchoring titin in Z disc of the sarcomere, and is known to cause LGMD2G, a rare muscle disorder characterised by proximal and distal lower limb weakness, calf hypertrophy and loss of ambulation. A total of 300 individuals with ARLGMD were recruited for this study. Among these we identified 8 clinically well characterised LGMD2G cases from 7 unrelated Dravidian families. Clinical examination revealed predominantly proximo - distal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…On the contrary, distal involvement is frequently described in LGMD2G patients, sometimes also at early stages [6-14-19], especially in lower limbs, presenting with foot-drop and involvement of tibialis anterior muscles. As well as in our patient, this feature was predominant also in other subjects with LGMD2G [6][7][8][9][10][11][12][13][14][15][16][17]. Respiratory involvement or cardiomyopathy was not reported in both cases, consistently with the majority of previous reports; extrasystolia had been described only in the Turkish patient.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, distal involvement is frequently described in LGMD2G patients, sometimes also at early stages [6-14-19], especially in lower limbs, presenting with foot-drop and involvement of tibialis anterior muscles. As well as in our patient, this feature was predominant also in other subjects with LGMD2G [6][7][8][9][10][11][12][13][14][15][16][17]. Respiratory involvement or cardiomyopathy was not reported in both cases, consistently with the majority of previous reports; extrasystolia had been described only in the Turkish patient.…”
Section: Discussionsupporting
confidence: 92%
“…In our cohort, all four patients with LGMD2G carried the same homozygous hot spot mutation, c.26_33dup (p.Glu12Argfs*20), which has previously been reported only in three Chinese patients and one Indian patient [30,31]. Taken together, our results further emphasize the potential founder effect of this mutation in East and South Asia.…”
Section: Discussionsupporting
confidence: 85%
“…A cohort study of 300 patients with autosomal recessive LGMD identified eight patients with LGMD 2G, who either had no or reduced telethonin protein levels [ 160 ]. Clinical features were predominantly progressive proximo-distal muscle weakness, scapular winging and calf hypertrophy.…”
Section: Z-disc Proteins In Myopathy and Cardiomyopathymentioning
confidence: 99%
“…A number of studies indicate a causative role of homozygous TCAP variants resulting in premature stop codons in LGMD 2G. Analyses of skeletal muscle biopsies suggest lack of functional telethonin protein [ 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ]. However, findings depend on the epitopes of the antibodies used, so it is currently not clear how much nonsense mediate decay contributes to the disease mechanism.…”
Section: Z-disc Proteins In Myopathy and Cardiomyopathymentioning
confidence: 99%